ALOX5 exhibits anti-tumor and drug-sensitizing effects in MLL-rearranged leukemia - Yungui Wang (Nature Portfolio, 2017)
Abstract MLL-rearranged acute myeloid leukemia (AML) remains a fatal disease with a high rate of relapse and therapeutic failure due to chemotherapy resistance. In analysis of our Affymetrix microarray profiling and chromatin immunoprecipitation (ChIP) assays, we found that ALOX5 is especially down-regulated in MLL-rearranged AML, via transcription repression mediated by Polycomb repressive complex 2 (PRC2). Colony forming/replating and bone marrow transplantation (BMT) assays showed that Alox5 exhibited a moderate anti-tumor effect both in vitro and in vivo. Strikingly, leukemic cells with Alox5 overexpression showed a significantly higher sensitivity to the standard chemotherapeutic agents, i.e., doxorubicin (DOX) and cytarabine (Ara-C). The drug-sensitizing role of Alox5 was further confirmed in human and murine MLL-rearranged AML cell models in vitro, as well as in the in vivo MLL-rearranged AML BMT model coupled with treatment of “5 + 3” (i.e. DOX plus Ara-C) regimen. Stat and K-Ras signaling pathways were negatively correlated with Alox5 overexpression in MLL-AF9-leukemic blast cells; inhibition of the above signaling pathways mimicked the drug-sensitizing effect of ALOX5 in AML cells. Collectively, our work shows that ALOX5 plays a moderate anti-tumor role and functions as a drug sensitizer, with a therapeutic potential, in MLL-rearranged AML.